ChemInform Abstract: Sodium‐Iodoxybenzoate Mediated Highly Chemoselective Aziridination of Olefins. Issue 4 (January 2015) - Bakthavachalam, Ananthan; Chuang, Hui‐Chun; Yan, Tu‐Hsin
Abstract Sodium 2‐iodoxybenzoate as a highly specific oxidant for N‐aminophthalimide (II) is utilized for the first time to generate a highly chemoselective aziridination reagent.